What the eyes can’t see: the future according to Monteiro Lobato - Medeiros, Bruno Franco (História da Historiografia: International Journal of Theory and History of Historiography, 2021)
Over the last years, Monteiro Lobato has been rightfully accused by Brazilian and Latin American scholars of expressing racist and eugenic ideas in his body of work. In this article, we take a step further and add to this traditional portrait of his literary production an analysis of the impact of a new set of technological media during the first decades of the twentieth century on his writings. We discuss how these two main issues – i.e., technology and race – played out in Lobato’s historical representation of Brazil’s past and future and the influence that the United States could play in it. We show how a revisionary and racist version of the United States’ history and the ideal of an American technological prosperity in the 1920s inspired one of Lobato’s most contentious novels, the technological dystopia O Presidente Negro, ou O Choque das Raças, published in 1926.